Similar patterns of parental provisioning in a monogamous and a polygynous population of the House Wren - Llambias, Paulo (2012)
In the House Wren (Troglodytes aedon), polygyny is characterized by males' partial desertion, males providing little or no help in feeding the nestlings of one of their mates. We evaluated whether contributions to feeding nestlings and patterns of provisioning by partially deserted females can explain geographic variation in the species' rate of polygyny. From 2003 to 2007, we studied two populations differing in polygyny rate (U.S., 40%; Argentina, 2%). We induced polygyny in the monogamous population by removing males from their territories before the onset of egg laying. We predicted that if patterns of parental care are related to variation in the social mating system, monogamous males should contribute more in the monogamous population than in the polygynous population, in the monogamous population partially deserted females should not compensate for the lack of help by feeding at rates higher than do aided females, and partial desertion should be more costly in the monogamous population. Monogamous males of the two populations did not differ significantly in their contribution to provisioning. Females' pattern of provisioning was also similar; partially deserted females fed nestlings at a rate higher than did aided females but did not fully compensate for the lack of help. Furthermore, the cost of male desertion seems greater in the polygynous population, as the breeding and fledging success of poorly aided females were lower. We suggest that the male's contributions to parental care and the patterns of unaided females' feeding cannot explain the geographic variation in the House Wren's mating systems.